A critical examination of the definition and implementation of Riqab (Slavery) by a selected Bait al-Mal in Malaysia - Awang, Abdul Bari; Sarif, Suhaimi Mhd; Ismail, Yusof (2010)
Riqab (slavery) is one of the standard categories of Zakat expenditure sanctioned by Islam. Unlike in the old days where the incidence of slavery was common, modern life might find cases of slavery alien, almost non-existent. This study attempts to revisit the particular category as being managed by one of the Bait al-Mal’s in Malaysia. Objective: The study attempts to propose the core concept of riqab in the Islamic literature, and verify it with the definition adopted by and actual distribution practiced by the Mal. Issues: There are two main issues that challenge intellectuals and average people in this study: (1) Whether the definition of riqab adopted by the Mal is well supported by the literature; (2) Whether the Mal’s recipients under riqab category are consistent with the definition. Methodology: The study will present analysis of the actual data available with the Mal. In addition, it will obtain experts’ views on the same issues. To further evaluate on whether ordinary Muslims perceive acceptability or otherwise of the examples of riqab recipients adopted by the Mal, the study proposes to administer a short questionnaire on Muslim students of a public university. Significance: The study is unique both in terms of novelty of the topic and attempts by the Mal to apply the concept in an apparently non-riqabic contemporary environment.